R.A.F.T (ROLE,AUDIENCE, FORMAT AND TOPIC) AS WRITING STRATEGY TO TEACH WRITING DESCRIPTIVE TEXT FOR TENTH GRADES OF SMAN 12 SURABAYA (RETAIN, 2016)
R.A.F.T (ROLE,AUDIENCE, FORMAT AND TOPIC) AS WRITING STRATEGY TO TEACH WRITING DESCRIPTIVE TEXT FOR TENTH GRADES OF SMAN 12 SURABAYA EMI DAMAYANTI English Education, Language and Art Faculty, State University of Surabaya emidamayanti@mhs.unesa.ac.id Nur Chakim , S. Pd., M. Pd. English Education, Language and Art Faculty, State University of Surabaya Nurchakim@unesa.ac.id Abstrak RAFT adalah strategi menulis yang focus pada sudut pandang siswa sebagai penulis, pembaca yang dituju, bentuk penulisan yang menarik dan topic yang dituliskan. Penelitian ini merupakan penelitian deskriptif kualitatif. Subjek penelitian ini adalah siswa kelas sepuluh IPA 5 SMAN 12 Surabaya. Data penelitian ini diperoleh melalui field notes, observasi checklist, hasil tugas menulis siswa dan hasil interview. Proses implementasi strategi RAFT untuk menulis teks deskriptif berhasil diimplementasikan. Siswa menunjukan peningkatan dalam menulis teks deskriptif dan menunjukan respon positif terhadap pelajaran menulis dalam bahasa inggris. Peneliti menemukan bahwa strategi ini membantu siswa dalam mengembangkan proses berfikir kreatif dan juga membantu meningkatkan motivasi siswa dalam menulis. Hasil menulis siswa menunjukan bahwa siswa lebih nyaman dalam menulis dan lebih memahami materi pelajaran. Berdasarkan rubric penilaian menulis oleh Jacob (1981) terdapat empat kategori menulis yaitu sangat baik, baik, cukup baik dan kurang. Dapat disimpulkan bahwa strategi role, audience, format dan topic (RAFT) dapat meningkatkan kemampuan menulis teks deskriptif siswa. Strategi ini juga mendorong siswa untuk menulis dan juga mengembangkan proses berfikir kreatif. Selain itu, strategi ini mampu menciptakan suasana kelas yang aktif dan menyenangkan. Kata kunci : Menulis, teks deskriptif, strategi RAFT Abstract RAFT is writing strategy focuses on students’ point of view as a writer, the addressed audience, unique format of writing and stated topic. The researcher conducted this study as descriptive qualitative research. The subject of the study is tenth grade students of SMAN 12 Surabaya. The students are come from science class 5. The data of this study are result from field notes, observation checklist, students writing task, and interview. The process of teaching writing descriptive text using RAFT strategy was successfully implemented. Students show improvement in writing performance and their perception of English. Furthermore, they show positive attitude toward the strategy and English subject. The researcher found the strategy was interesting and it promoted students creative thinking. This research has proved that RAFT strategy can help students to improve writing ability especially in writing descriptive text. Student task result showed that the way they wrote is much more comfortable and they understand the material better. Based on writing Rubric by Jacob (1981), students writing task were included into four category, they are excellent to very good, very good to average, average to poor and very poor. Finally, it can be concluded that role, audience, format and topic (RAFT) strategy is helpful to improve student descriptive writing ability. This strategy also encourages students to write as well as promotes student creative thinking and motivation. Moreover, it can make classroom activity become more active and enjoyable. Keywords: writing, descriptive text, and RAFT writing strategy.